The effect of goal-directed fluid therapy combines closed-loop anesthesia management on postoperative rehabilitation of patients undergoing laparoscopic pancreaticoduodenectomy - Di, Li-li; Wang, Yu-xi; Ma, Shu-xian; Wu, Wen-hao; Sun, Na; Wang, Zi-chen; Zhang, Ya-wen; Huang, Li-ning (Journal of clinical anesthesia, 2020)
Furthermore, improper intraoperative anesthetic and liquid management will prolong the patient's recovery time and increase the incidence of postoperative complications [4]. [...]we aim to compare the precision anesthesia management of GDFT combined CLADS with traditional methods in laparoscopic pancreatoduodenectomy and to investigate the effects of the former on postoperative recovery. There are advantages and disadvantages in endoscopic surgery, and fine perioperative management can affect the prognosis of patients. [...]it is of great clinical significance to explore GDFT and CLADS. According to our results, we conclude that the CLADS combined with GDFT can be safely applied to laparoscopic pancreatoduodenectomy to achieve accurate intraoperative anesthesia management and improve patients' prognosis.